An isopentenyl-substituted flavonoid norartocarpin activates Nrf2 signalling pathway and prevents oxidative insults in human lung epithelial cells. (4th March 2019) - Yang, Wen-Jing; He, Ji-Xiang; Zhou, Ming-Xing; Huang, Min; Wang, Shu-Qi; Wang, Xiao-Ning; Lou, Hong-Xiang; Ren, Dong-Mei; Shen, Tao
Abstract: The nuclear factor erythroid 2-related factor 2 (Nrf2) plays a crucial role in regulating the intracellular oxidative stress, and thus activation of Nrf2 by nature-derived molecules effectively alleviates the pathological process of oxidative stress-induced chronic diseases. The isopentenyl-substituted flavonoid norartocarpin (NOR) induced the activity of NAD(P)H: quinone reductase (QR), implying that it might be a potential Nrf2 activator. Further studies indicated that NOR upregulated the protein levels of Nrf2 and its downstream genes, NAD(P)H quinone oxidoreductase 1 (NQO1), and γ-glutamyl cysteine synthetase (GCLM) through facilitating the nuclear translocation of Nrf2 and enhancing Nrf2 protein stability. NOR-induced activation of Nrf2 pathway was associated with multiple upstream kinases, including mitogen-activated protein kinase (MAPK), phosphatidylinositol-4, 5-bisphosphate 3-kinase (PI3K), protein kinase C (PKC), and protein kinase R-like endoplasmic reticulum kinase (PERK). Moreover, NOR protected human lung epithelial Beas-2B cells against sodium arsenite [As(III)]-induced cytotoxicity in an Nrf2-dependent manner. Collectively, NOR was firstly identified to be an Nrf2 activator, which demonstrated the capability of preventing oxidative insults in human lung epithelial cells.